Development Of AREAS (Augmented Reality Ecosystem) On Ecosystem Material To Improve Digital Literacy Skills Of Class V Students Of Elementary School - Fadiah, Tiara Aulia; Suhartini, Erna; Haerani, Rosita Putri Rahmi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
The lack of integration of technology-based learning media in learning causes low student digital literacy. The objectives of this study are: (1) to determine the feasibility of AREAS, (2) to determine students' response to AREAS, (3) to determine students' digital literacy skills after using AREAS. This research is a development research based on the ADDIE model, namely analyze, design, develop, implement, and evaluate. The instruments utilized in this research are media expert validation questionnaire, a material expert validation questionnaire, a student response questionnaire, and a digital literacy test assessment. Observation, interviews, and questionnaires were employed to gather data for this study. The data analysis technique used was quantitative data analysis and digital literacy ability analysis. The results showed that AREAS was feasible to use with a feasibility percentage of 93.1%, a student response of 90.9%, and a digital literacy n-gain score of 0.61 in the “Medium” category. It can be concluded that AREAS is very feasible to use in learning and effective enough to improve the digital literacy of class V C students of SDN 011 Samarinda Kota. The development of original interactive learning media by creating augmented reality assets themselves is recommended for future research.